Anew mid-ripening table grape cultivar Puyuan Qinxiang - XIANG Jiang; CHENG Jianhui; WEI Lingzhu; ZHENG Ting; WU Jiang (Guoshu xuebao, 2025)
Puyuan Qinxiang is a new mid-ripening table grape variety with excellent appearance derived from a cross between Muscat Hamburg (♀) and 09-05-3 (♂) in 2024 at the experimental field. A total of 866 hybrid seeds were harvested through artificial pollination hybridization in 2014. The seeds were sown in nutrition cups to obtain 298 hybrid seedlings and then they were transplanted in the grape breeding resource nursery in spring 2015. The original plant numbered 191 was selected as the superior line in 2017 due to the high yield, bright red skin color, large berry, crispy meat and strong complex aroma. After regional adaptability testing at three sites (including Xiaoshan, Haining and Yinzhou) over three years from 2021 to 2023, it was finally named Puyuan Qinxiang. It is a diploid cultivar with bisexual flowers. The tender tips are half-open with dense creeping villi and weak anthocyanins. The upper surface of the young leaves is light reddish brown, and the density of creeping villi between the main veins on the back is moderate. The new canes are semierect and the color of dorsal and ventral sides of internodes is green and red, respectively. The mature leaves are green and pentagonal shaped with 5 lobes. The shape of the serrations is convex on both sides, and the aspect ratio of the serrations is small. Both the upper and lower lateral sinus on mature leaves overlap. The petiole sinus is slightly open. The color intensity of anthocyanin in leaf veins is moderate. The creeping villi between the dorsal main veins and the upright villi on the dorsal main veins are both absent or extremely sparse. The grape clusters are conical in shape with uncompact density and without shoulders. The fruit clusters are large and relatively uniform with the average weight of 651.47 g. The berries are elliptical in shape and bright red in color with consistent sizes and maturity. The average weight of single berry is 9.45 g, and the maximum weight is 12.00 g. The peel is slightly thin covered by thin fruit powder. The flesh is crispy, without any flesh sacs, and has a rich and complex aroma. The number of seeds in a berry is 3-4, the fruit brush is longer, and it is difficult to separate the berries from the stem. The soluble solid content of berries is 22.0%, the titratable acid content is 0.15% and the vitamin C content is 32.2 mg·kg-1. In the Haining area of Zhejiang province, under facility cultivation conditions, it begins to sprout in mid-March, bloom in late April, and mature in mid-August. Normally, it takes 151-157 days from bud sprouting to berry ripening, making it a medium ripening variety. The growth potential of canes is moderate and not excessive, with a germination rate of 89.50% and a fruiting cane rate of 94.55%. The first inflorescence usually emerges on the fourth or fifth node and average number of inflorescences per fruiting cane is 1.56. The variety shows excellent abilities of flower bud differentiation, fruit setting and secondary fruiting. The yield is suggested to be controlled within 1250-1500 kg per 666.7 m2 to ensure berries to set color well. The middle or long cane pruning and T-shape should be used for Puyuan Qinxiang. It is suitable for greenhouse cultivation in Zhejiang and similar areas.